2018
DOI: 10.1371/journal.pone.0200105
|View full text |Cite
|
Sign up to set email alerts
|

Influence of social network on drug use among clients of methadone maintenance treatment centers in Kunming, China

Abstract: AimsTo examine drug use behavior of clients attending Methadone Maintenance Treatment (MMT) programs and its relationship with the clients’ social network characteristics.DesignCross-sectional study.SettingFour MMT clinics in Kunming, Yunnan province, China.Participants324 consecutive MMT clients.MeasurementsA structured, self-completed questionnaire on background characteristics and existing social network. Current drug use was assessed by urine test for opiate metabolites.AnalysisThe association between clie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 49 publications
1
28
1
Order By: Relevance
“…We infer that this is the result of connections with significant others, including the multi-disciplinary project team, peers and family members. These kinds of connections have been found to reduce feelings of stigmatisation and marginalisation and allow for life normalisation [57,58]. While the analysis did not indicate any notable change in overall physical health, it is useful to bear in mind that there was low HIV prevalence at baseline, which did not change after 6 months.…”
Section: Changes In Quality Of Lifementioning
confidence: 94%
“…We infer that this is the result of connections with significant others, including the multi-disciplinary project team, peers and family members. These kinds of connections have been found to reduce feelings of stigmatisation and marginalisation and allow for life normalisation [57,58]. While the analysis did not indicate any notable change in overall physical health, it is useful to bear in mind that there was low HIV prevalence at baseline, which did not change after 6 months.…”
Section: Changes In Quality Of Lifementioning
confidence: 94%
“…This can be a barrier to reacceptance by family members. A previous study also indicated that clients with a social network including members using drugs were more likely to concurrently use drugs [48]. Getting out of drug-addicted social relationships can not only help avoid relapse triggers but can also deliver a signal to their family that they are free from drugs in a turn to bring a more positive view of their relationships.…”
Section: Discussionmentioning
confidence: 98%
“…Ethnicity was also associated with social connections, as reported previously that, ethnic minorities preferred to build racial homophilic connections. [19] Yet such social relationship can be a double-edged sword—emotional support from network members could offer emotional support which in turn reduced heroin use and encouragement and discussion on HIV risks with peers would reduce engagement in sexual risk behaviours; [2223] on the other hand, such relationships may facilitate needle sharing practice,[24] thereby hampering the effort of harm reduction and HIV prevention.…”
Section: Discussionmentioning
confidence: 99%